“The Grind Never Stops”: Mental Health and Expectations of Productivity in the North American University - Wiley, Adrianna (Anthropologica, 2023)
Using a critical phenomenology approach, I explore how the neoliberal social context of the North American university produces normative expectations which both interact with and pattern student experiences and understandings of mental health struggles in this environment. The data I analyze comes from semi-structured interviews with 24 university students between 18 and 24 years of age who self-identify as experiencing mental health struggles, as well as participant observation at university wellness events. In this context, both students and the university understand wellness as the ability to maintain constant academic productivity. While university wellness programming promotes goal-oriented individualized “self”-care as the gold standard for attaining and maintaining wellness, students often view self-care activities as unproductive, instead prioritizing academic productivity over subjective well-being in striving to maintain an image as the “good” student. I argue that understanding mental health in this way both causes and exacerbates harm, introducing the conceptual contrast between “Student Wellness”—academic success—and “Human Wellness”—subjective well-being—as a means of understanding how university attempts to increase wellness often support neoliberal agendas to the detriment of their students’ well-being.